Analisis Pemangku Kepentingan dan Jaringan Sosial Menuju Pengelolaan Multipihak di Kabupaten Solok, Sumatera Barat - Qori Pebrial Ilham; Herry Purnomo; Tri Nugroho (Institut Pertanian Bogor, 2016)
Protected Forest Management Unit (PFMU) of Solok is one of 120 FMU Model that has been set by the government through Ministry of Environment and Forestry (MoEF). Community settlements (Nagari) were around and inside the FMU. Additionally, the existence of the FMU as a new institution in forest management cause different interpretation of the various stakeholders. The objective of this research was to identifying stakeholders and their interest and analyzing the patterns of relationship of stakeholders involved in the management of PFMU Solok. This research was conducted based on stakeholder analysis and social network analysis. Stakeholders involved in management of PFMU Solok have diverse interests and power. There were 22 stakeholders identified, in which 2 were classified as key players, 10 as subject, 4 as context setter, and 6 as crowd. Interaction pattern of stakeholders in the form of information flow was not spread evenly. The result shows that there were many stakeholder in the management of PFMU Solok. Multistakeholder forest management can be an alternative management model to integrate interests of stakeholders and equally distribute information.